Deconcentration of General Government Affairs in Support of National Unity and Integrity in Indonesia: a Systematic Literature Review - Vandyarman Priyanda; Mainita Hidayati (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2026)
This research aims to conduct a systematic literature review of deconcentration policies on general government affairs (GGA) to support National Cohesion (NC) in Indonesia. This research used Kitchenham and Charters' (2007) systematic literature review (SLR) protocol and bibliometric analysis. The SLR results are then mapped by developing an actor-based conceptual model with roles that can be implemented as a quintuple helix diagram according to expert validation. The findings of this research are The deconcentration policy model in GGA consists of 3 dimensions and 11 sub-dimensions. The three dimensions are governance, public policy, and NC. The 11 sub-dimensions are as follows: residual power; national insight; national politics; national alert; conflict management; central and regional relations; policy implementation; deconcentration; national identity; National defence; politics and stability. The main actors in this model are the government, legislature, private sector/investors, universities/academics, GGA support forums, and representatives (religious leaders, community leaders, and traditional leaders). The originality of this research is that it can map the results of previous research related to the implementation of GGA in a comprehensive systematic manner by presenting the network of actors involved in implementing GGA in Indonesia based on prior research. Keywords: Deconcentration, Systematic Literatur Review, General Government Affairs (GGA), National Cohesion (NC)